Faktor-Faktor Yang Pendorong Dan Penghambat Usaha Ternak Ayam Potong Bermitra Dengan PT. Wacana Jaya - Henny Risnawati; Wianaya Purwanti; Asep Saifudin (Cakrawala Akuntansi & Manajemen, 2022)
The purpose of this study was to determine the factors that encourage and inhibit the chicken livestock business in the partnership of Sinar Jaya Partners Ltd. The research approach used in this study was a qualitative method. The respondents consisted of three livestock businesses that are partners of Sinar Jaya Partners Ltd. The result showed that the main factors that encouraged and hindered the willingness of entrepreneurs to become partners of Mitra Sinar Jaya Ltd are: 1) Costs incurred by farmers in the broiler business in partnership with Mitra Sinar Jaya Ltd, namely the average number of fixed costs and the average amount; 2) The average total net income per harvest obtained by broiler breeders in the partnership of Sinar Jaya Partners Ltd